Design and Development of High Power Broad Band Dry RF Load - Nayek, Narugopal; Naik, Arvind; Phatangare, Manoj; Tiwari, T. (Defence Science Journal, 2021)
High power S-Band ferrite based RF load is designed and developed which is capable of handling 3 kW average power at operating frequency 2998±20 MHz . Electrical and thermal design is carried out using CST Studio Suite. Mechanical parts are fabricated according to the design. Water cooling is provided to the absorbing ferrites to support high power operation. Various RF load parts are fabricated, chemically cleaned and brazed. The experimental return loss better than 30 dB for a bandwidth of 250 MHz is achieved. The numerical and experimental results are discussed and presented in this paper.